(untitled) (Modern information system and technologies, 2018)
In this article was analysis the basic means of test cases, their structure and principles of implementation. Also considered condition of test cases in the modern realities of developing program products. Was demonstrate the valuation model of effectiveness implementation test cases with depending on the type and volume of the project.